2021
DOI: 10.1029/2020jb021042
|View full text |Cite
|
Sign up to set email alerts
|

The Viscous and Ohmic Damping of the Earth's Free Core Nutation

Abstract: The cause for the damping of the Earth's free core nutation (FCN) and the free inner core nutation eigenmodes has been a matter of debate since the earliest reliable estimations from nutation observations were made available. Numerical studies are difficult given the extreme values of some of the parameters associated with the Earth's fluid outer core, where important energy dissipation mechanisms can take place. We present a fully 3D numerical model for the FCN capable of describing accurately viscous and Ohm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
(78 reference statements)
0
13
0
Order By: Relevance
“…The restoring force for inertial waves is the Coriolis force (Rekier et al 2019(Rekier et al , 2020. There are many waves that are more or less damped, and that show different repartitioning of the energy between the core and the mantle (Triana et al 2019(Triana et al , 2021.…”
Section: Cmb From Geodesymentioning
confidence: 99%
“…The restoring force for inertial waves is the Coriolis force (Rekier et al 2019(Rekier et al , 2020. There are many waves that are more or less damped, and that show different repartitioning of the energy between the core and the mantle (Triana et al 2019(Triana et al , 2021.…”
Section: Cmb From Geodesymentioning
confidence: 99%
“…However, for short length scales, where the viscous forces start to exceed inertial forces, and especially in the boundary layers, the effect of viscous dissipation may become important (Schaeffer et al 2017). Further analysis of waves associated with rapid SV observations can help determine where the energy of the wave is dissipated, whether it be within a boundary layer (Triana et al 2021) or in the internal shear layers as claimed by Buffett (2010). This latter mechanism was found to be inefficient by Lin and Ogilvie (2020), who observe in numerical simulations (for values of Ek as low as 10 −11 ) a too weak dissipation in conical shear layers, in order to explain the damping of the free inner core nutation.…”
Section: Excitation and Dissipation Of Waves/modesmentioning
confidence: 99%
“…However, we note from figures 2 and 4 that the decay rates from Ohmic The effect of the magnetic field on these modes has been the subject of several recent studies. Focusing on the spin-over node, [47] find that for Λ ≥ 1 and low Pm, Ohmic and viscous dissipation contribute nearly equally to the decay rate when the imposed field is uniform and the fluid is contained in a Earth-like shell with rigid boundary conditions. Working with stress-free boundary conditions in a spherical shell, [48] found that Ohmic dissipation was the predominant mechanism when P m = 10 −6 as in the Earth, Λ ≥ 10 −1 and the Ekman number E was 10 −9 .…”
Section: (G) Damping Of Fast Modesmentioning
confidence: 99%